Production cost of ice slurry using a saline solution and different ice mass fractions, applied to “Perico” (Coryphaena Hippurus) artisanal fishing in Peru - Milón Guzmán, Juan José (2021)
2021 6th International Conference on Sustainable and Renewable Energy Engineering, ICSREE 2021